Dengue-specific serotype related to clinical severity during the 2012/2013 epidemic in centre of Brazil - Benigno A. M. Rocha; Adriana O. Guilarde; Angela F. L. T. Argolo; Marianna Peres Tassara; Lucimeire A. da Silveira; Isabela C. Junqueira; Marília D. Turchi; Valéria C. R. Féres; Celina M. T. Martelli (BMC, 2017)
Abstract Multilingual abstracts Please see Additional file 1 for translations of the abstract into the five official working languages of the United Nations. Background Currently, in Brazil, there is a co-circulation of the four dengue (DENV-1 to DENV-4) serotypes. This study aimed to assess whether different serotypes and antibody response patterns were associated with the severity of the disease during a dengue outbreak, which occurred in 2012/2013 in centre of Brazil. Methods We conducted a prospective study with 452 patients with laboratory confirmed dengue in central Brazil, from January 2012 to July 2013. The clinical outcome was the severity of cases: dengue, dengue with warning signs, and severe dengue. The patients were evaluated at three different moments. Blood sampling for laboratory testing and confirmatory tests for dengue infection were performed. We performed a multinomial analysis considering the three categories of the dependent variable, as outlined above. The odds ratios (ORs) were calculated. A multinomial logistic regression model was applied for variables with a P-value <0.20. Statistical analysis was performed with STATA 12.0 software. Results Four hundred fifty-two patients (452/632, 71.5%) were diagnosed with dengue. The dengue virus (DENV) serotypes were identified in 243 cases. DENV-4 was detected in 135 patients (55.6%), DENV-1 in 91 (37.4%), DENV-3 in 13 (5.3%), and DENV-2 in 4 (1.6%). Patients with the DENV-1 serotype were more prone to present with several clinical and laboratory features as compared with DENV-4 patients, including spontaneous bleeding (P = 0.03), intense abdominal pain (P = 0.004), neurological symptoms (P = 0.09), and thrombocytopenia (P = 0.01). Secondary infection was more predominant among DENV-4 cases (80.0%) compared with DENV-1 cases (62.3%) (P = 0.03). The univariate analysis showed that females (OR = 2.12; 95% CI: 1.44-3.13; P < 0.01) had a higher risk of having dengue with warning signs. The multinomial analysis showed that severe dengue cases with secondary infection had an adjusted OR of 2.80 (95% CI: 0.78-10.00; P = 0.113) as compared with dengue fever with primary infection when adjusted for age and sex. Conclusion The current data show that 5.8% of patients recruited for treatment in healthcare centres and hospitals during the study period had severe dengue. DENV-4 was the predominant serotype, followed by DENV-1, in a large outbreak of dengue in central Brazil. Our findings contribute to the understanding of clinical differences and immune status related to the serotypes DENV-1 and DENV-4 in central of Brazil.